Safeguarding and using fruit and vegetable biodiversity - Zonneveld, Maarten van; Volk, Gayle M.; Dulloo, Mohammad Ehsan; Kindt, Roeland; Mayes, Sean; Quintero, Marcela; Choudhury, Dhrupad; Achigan-Dako, Enoch G.; Guarino, Luigi (Association of International Research and Development Centers for Agriculture (AIRCA), 2021)
Fruit and vegetable species and varieties, their wild relatives, and pollinators and other associated organisms, underpin diverse food production systems and contribute to worldwide health and nutrition. This biodiversity, however, is threatened, remains poorly conserved, and is largely undocumented. Its loss leads to a narrowing of new crop options, reduced variation for breeding, and yield gaps due to pollinator decline. This constraints the supply of climate-resilient and nutritious foods to the global human population and limits long-term progress towards the 2030 Sustainable Development Goals and any future goals set thereafter. It will require awareness raising globally to safeguard and sustainably use fruit and vegetable biodiversity and a global rescue plan to reduce and reverse the decline in this biodiversity. Success will depend on a global partnership of custodians and users of fruit and vegetable biodiversity, and requires an investment of at least 250 million USD over 10 years.